A proposal of multi-agent system development framework for cooperative problem solving and its experimental evaluation. (15th November 2007) - Sawamoto, Jun; Tsuji, Hidekazu; Koizumi, Hisao
The current status of agent research is that many researches are for a specific application domain and are lacking in generality, and it is hard to apply the framework of the existing research to other fields. It is thought that practical usage of agents is in an immature state that there are few practical application examples and the system development methodology is not sufficient. In this research, the cooperative problem solving system by multi-agents is shown as an application development framework. Then, we present usage of templates of the agent model and the task model as the development support technique. And the evaluation according to an application construction experiment in a planning problem or the field of network community support is discussed.